Monarchy, revolution and refugees Laos, Thailand, Argentina, Kampuchea : a personal view - Irvine, Walter (River Books, 2022)
Walter Irvine's account places his personal experiences against the political and cultural changes that surrounded the Lao and Cambodian revolutions of the 1970s and 80s, giving particular attention to refugee movements and the impact. Irvine's professional involvement as teacher in Laos, social anthropologist in Thailand and UNHCR official in Argentina gives him an insiders understanding of the specificity of culture, the dynamics of political change, the realities of forced exile, and the challenges of refugee work. His description of revisiting Indochina in 2016 puts the account of the early period into perspective
Keywords: Geschichte 1972-2016; Geschichte 1982-1984; Lao; Flüchtling; Politischer Wandel; Kulturwandel; Argentinien; Indochina; Irvine, Walter / Travel / Laos; Irvine, Walter / Travel / Cambodia; Irvine, Walter / Travel / Argentina; Laos / Description and travel; Cambodia / Description and travel; Argentina / Description and travel; Travel; Argentina; Cambodia; Laos; Erlebnisbericht